Oncogenes and Carcinogenesis 2019
DOI: 10.5772/intechopen.80925
|View full text |Cite
|
Sign up to set email alerts
|

The AIB1/NCOA3/SRC-3 Oncogene

Abstract: A member of the NCOA/SRC/p160 co-activator family, AIB1 is amplified and overexpressed in multiple cancer types, notably breast, ovarian, and pancreatic cancer. Common to all members of the NCOA/SRC/p160 family are bHLH-PAS, receptor interaction, and CBP/p300 interacting activation domains. The protein acts as a scaffold to support the transcriptional activity of many DNA binding transcription factors, such as the ER, AP-1, E2F, NFκB, and TEADs. In doing so, the multi-domain protein facilitates chromatin remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…In normal human breast tissue, AIB1 levels are low, but significantly increase at the DCIS stage of breast cancer [6]. AIB1 functions as a transcription co-activator and has been shown to interact with many transcription factors, such as nuclear receptors, NFjB, and E2F, to promote transcription in physiology and disease contexts [7]. Further, we and others have shown that AIB1 can also recruit transcription repressor proteins, such as the putative tumor suppressor ANCO1/ANKRD11, to suppress transcription at select sites [8][9][10][11], which may also contribute to malignant progression.…”
Section: Introductionmentioning
confidence: 99%
“…In normal human breast tissue, AIB1 levels are low, but significantly increase at the DCIS stage of breast cancer [6]. AIB1 functions as a transcription co-activator and has been shown to interact with many transcription factors, such as nuclear receptors, NFjB, and E2F, to promote transcription in physiology and disease contexts [7]. Further, we and others have shown that AIB1 can also recruit transcription repressor proteins, such as the putative tumor suppressor ANCO1/ANKRD11, to suppress transcription at select sites [8][9][10][11], which may also contribute to malignant progression.…”
Section: Introductionmentioning
confidence: 99%
“…AIB1 is known to act as a coactivator for several transcription factors other than the ER. Besides E2F and Ets interactions described above, AIB1 increases the expression of AP-1 (activator protein 1), TEADs and NF-κB (nuclear factor kappa B) dependent target genes, among others (reviewed in 145 ). Briefly, AIB1 coactivation of AP-1 promoted transcription of matrix metalloproteinases and increased invasiveness of human breast cancer cells ( 146 ).…”
Section: Aib1 Erα-independent Activitiesmentioning
confidence: 99%